Low affinity nerve growth factor receptor gene co-segregates with decreased bodyweight and increased left ventricular weight in spontaneously hypertensive rats - Kapuscinski, M K; Nemoto, K; Ueyama, T; Charchar, F; Kageyama, H; Fukumachi, K; Sekimoto, M; Senba, E; Tomita, T; Tomita, I; Harrap, S B (Clinical and experimental pharmacology & physiology, 1996)
1. The sympathetic nervous system influences the cardiovascular and hormonal systems and sympathetic innervation is dependent on nerve growth factor (NGF). The NGF gene is linked genetically to high blood pressure in the spontaneously hypertensive rat (SHR) and there exists a mutation in the SHR low affinity NGF receptor (LNGFR) gene. 2. To determine whether the LNGFR mutation was linked genetically with cardiovascular phenotypes we studied an F2 population derived from SHR and normotensive Donryu (DRY) rats. 3. Mean arterial pressure (MAP), left ventricular mass (LVM) and related phenotypes were measured in 127 20 week old male F2 rats and correlated with the inheritance of the SHR mutation (S) and/or the DRY allele (D) of the LNGFR. 4. Analysis of variance revealed that the S mutation was associated with a significantly lower bodyweight in F2 rats (P < 0.0001). 5. The S mutation was associated with a significant (P < 0.007) increase in LVM:bodyweight ratio, but not with differences in right ventricular or kidney weights corrected for bodyweight. We found no association between MAP and LNGFR alleles or genotypes. 6. These results suggest that the mutation in the signal peptide of LNGFR may serve as a useful marker for the analysis of genetic factor(s) involved in the differential determination of body size and heart weight.